2012
DOI: 10.2174/1876387101205010001
|View full text |Cite
|
Sign up to set email alerts
|

Small Scale Pilot Combustion Experiments with Wood Pellets – The Effect of Pellet Length

Abstract: Abstract:The primary objective of this study was to observe the effect of pellet length on utility and combustion temperature. Pellets with various lengths were combusted in a pellet stove. Pellet length was found to have a significant effect on the combustion temperature and stability. Increasing the length of pellets from 5.8mm to 13.1mm decreased the average burning temperature by 31% and flue gas temperature by 25%. The major determinants of combustion efficiency derived from pellet length were assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Pellet size (length) also affects the burning efficiency. Sikanen and Vilppo (2012) found that wood pellet burning temperature decreases by 31% and flue gas temperature by 25%, as the pellet length increases from 5.8 mm to 13.1 mm [28]. The use of binding agents as additives has been found to have an effect on the pellet length.…”
Section: Bulk Density and Pellet Sizementioning
confidence: 99%
“…Pellet size (length) also affects the burning efficiency. Sikanen and Vilppo (2012) found that wood pellet burning temperature decreases by 31% and flue gas temperature by 25%, as the pellet length increases from 5.8 mm to 13.1 mm [28]. The use of binding agents as additives has been found to have an effect on the pellet length.…”
Section: Bulk Density and Pellet Sizementioning
confidence: 99%
“…Reductions in mass flow rate and furnace temperature as well as an increase in lambda at increasing pellet length were also observed and discussed by Wöhler et al [8] and siKanen et al [10]. However, no adjustment to the fuel supply was made in either publication.…”
Section: Influence Of Pellet Lengthmentioning
confidence: 79%
“…Several recent studies analyzed the influence of individual physical fuel parameters in wood pellets and their effect on emissions from pellet stoves and boilers. For instance, the influence of pellet length on pellet stove emissions was investigated in Wöhler et al [8] and Kahlsa et al [9] and only on combustion performance (i.e., temperatures and fuel mass flow) by siKanen et al [10]. These studies showed that longer pellets may cause a lower throughput rate of the fuel as well as lower combustion chamber temperatures [8,10] which in this turn leads to increased gaseous and total particulate matter (TPM) emissions [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation